2020
DOI: 10.1038/s41467-020-14915-8
|View full text |Cite
|
Sign up to set email alerts
|

Photo splitting of bio-polyols and sugars to methanol and syngas

Abstract: Methanol is a clean liquid energy carrier of sunshine and a key platform chemical for the synthesis of olefins and aromatics. Herein, we report the conversion of biomass-derived polyols and sugars into methanol and syngas (CO+H 2) via UV light irradiation under room temperature, and the bio-syngas can be further used for the synthesis of methanol. The cellulose and even raw wood sawdust could be converted into methanol or syngas after hydrogenolysis or hydrolysis pretreatment. We find Cu dispersed on titanium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 39 publications
3
60
0
Order By: Relevance
“…These findings indicate that methanol also functions as the proton source in combination with photogenerated electrons for the reductive transformation of furfural (Scheme S2). Using methanol, a cheap solvent that can be derived from biomass, 20 as the hydrogen donor can avoid the use of high-pressure H 2 or corrosive formic acid, rendering the current process safe and environmentally friendly. 21,22 The selectivity of products strongly depended on the exposed facet.…”
Section: Furfural Conversion Over Tio 2 With Different Facetsmentioning
confidence: 99%
“…These findings indicate that methanol also functions as the proton source in combination with photogenerated electrons for the reductive transformation of furfural (Scheme S2). Using methanol, a cheap solvent that can be derived from biomass, 20 as the hydrogen donor can avoid the use of high-pressure H 2 or corrosive formic acid, rendering the current process safe and environmentally friendly. 21,22 The selectivity of products strongly depended on the exposed facet.…”
Section: Furfural Conversion Over Tio 2 With Different Facetsmentioning
confidence: 99%
“…Indeed, photocatalysis has recently shown encouraging potentials in the valorization of biomass feedstocks 45 . Wang and co-workers 46 reported the photocatalytic coproduction of diesel precursors and hydrogen from biomass-derived furans using Ru-doped ZnIn 2 S 4 catalysts, alkane formation from fatty acid over Pt/TiO 2 photocatalysts 47 , as well as the production of methanol and syngas from bio-polyols and sugars 48 . Reisner and co-workers 49 studied the photocatalytic conversion of lignocellulose into H 2 over cadmium sulfide quantum dots.…”
mentioning
confidence: 99%
“…17,18 Methanol (CH 3 OH) has wide application in chemical reactions, and can be easily produced from renewable sources such as biomass. 19 It has been reported that over 300 000 metric tons of methanol is annually produced from renewable resources in the United States. 20 Given that the functional group of -OH is stored in methanol, it can serve as a clean, efficient and renewable hydrogen source, which makes it a high-potential hydrogen source for HCO 3 − reduction.…”
Section: Introductionmentioning
confidence: 99%